MODEL PENDIDIKAN ENTREPRENEURSHIP DI PESANTREN API TEGALREJO MAGELANG - Ahyadi Ahyadi; Abdul Ghofur; Musthofa Musthofa; Sunjana Sunjana; Zainudin Zainudin (Balai Penelitian dan Pengembangan Agama Jakarta, 2021)
Pesantren have a significant role on national development, especially in the field of religious education. Apart from teaching religion, some Pesantren in Indonesia also provide their students with entrepreneurship education. One of Pesantren that provides entrepreneurship education is Pesantren API Tegalrejo Magelang. This study aims to determine the education model of entrepreneurship in Pesantren. This research is a qualitative type with a literature study approach. The research data analysis is described based on the data findings in a qualitative descriptive manner. The results of the study show that Pesantren API Tegalrejo Magelang has implemented entrepreneurship education. â€œPesantren Entrepreneurâ€ (PARTNER) was established since 2010 by KH. M. Yusuf Chudori. PARTNER graduates approximately 250 students of entrepreneurship every year. In the field of education, this Pesantren implement a specific curriculum on entrepreneurship. The models applied in the implementation of â€œPesantren Entrepreneurâ€ are observation, mentoring or soft brain wash, and workshop.